Computational characterization of hemorheology in the lenticulostriate arteries predicts the location of vessel rupture during hypertensive intracerebral hemorrhage - Zongkun Hou; XiaoFei Li; Peng Ren; Yuhua Gong; TingWang Guo; Paul R. Krafft; Shilei Hao; Bochu Wang (Brain Hemorrhages, 2022)
Hypertensive intracerebral hemorrhage (ICH) is commonly provoked by rupture of basal ganglia and thalamus supplying lenticulostriate arteries (LSAs). The purpose of this study was to identify regions within the LSAs that are prone to rupture. A two-dimensional mathematical model of the LSAs was created in order to identify the location of vascular rupture and a parallel-plate flow chamber was used to evaluate the role of shear stresses on endothelial cell damage. Areas within the LSAs that were prone to rupture were distal parts of the vessels supplying the basal ganglia and thalamus, those located in close proximity to the trunk of the middle cerebral artery (MCA), as well as the vessel wall at the bifurcation point of the LSAs. Furthermore, more severe endothelial cell damage was observed at the origin of the LSAs. This study identified susceptible sites of blood vessel rupture within the LSAs, which, in the future, could be used to anticipate and potentially prevent the occurrence of clinical hypertensive ICH.